1997
DOI: 10.1046/j.1365-2354.1997.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Beliefs, Attitudes and Preventive Behaviours of Nurses Working in the Community

Abstract: A study of nurses, comprising district, school and practice nurses and health visitors, working in the community was carried out in 1992/1993. The aims of the research included exploration of the nurses' beliefs about and attitudes to cancer and their own cancer preventive behaviours. Focus group methodology was used, with 11 discussion groups, totalling 86 nurses. Data were analysed qualitatively and reported in relation to emergent themes. The nurses found cancer a terrifying disease, dreading a personal dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
6
0
4
Order By: Relevance
“…The majority of words that respondents associated with cancer were negative, which reflects general perceptions of cancer as one of the most feared diseases (Kearney et al 2003). Studies have also found negative attitudes to cancer among healthcare professionals (Box & Anderson 1997;McCaughan & Parahoo 2000), but there is a dearth of literature regarding the views of social carers who are more likely than healthcare professionals to support people with learning disabilities in community settings. The relevance of exploring attitudes to cancer in this target population is threefold.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of words that respondents associated with cancer were negative, which reflects general perceptions of cancer as one of the most feared diseases (Kearney et al 2003). Studies have also found negative attitudes to cancer among healthcare professionals (Box & Anderson 1997;McCaughan & Parahoo 2000), but there is a dearth of literature regarding the views of social carers who are more likely than healthcare professionals to support people with learning disabilities in community settings. The relevance of exploring attitudes to cancer in this target population is threefold.…”
Section: Discussionmentioning
confidence: 99%
“…Some attention has previously been paid to the relationship between fatalistic beliefs and preventive behaviour. It has been shown that people in Western industrialized countries who are familiar with cancer prevention measures may nevertheless adopt fatalistic attitudes towards the disease (Box & Anderson 1997, Sheikh & Ogden 1998. In Clover et al's (1991) study among Australians, most respondents believed that lung and skin cancer were not preventable, although risk factors for these are well established and widely publicised.…”
Section: Discussionmentioning
confidence: 99%
“…Cette différence pouvant s'expliquer par des niveaux de connaissances différents. Les résultats sur les préjugés et stéréotypes sur le cancer révèlent généralement une absence de différence significative en fonction du genre, de la profession, de l'expérience clinique, ou de la formation spécialisée ou non en oncologie par exemple (e.g., Box & Anderson, 1997 ;Kearney et al, 2003 ;Simon et al, 2011). Les expériences personnelles et professionnelles avec les malades seraient les principaux facteurs déterminants des stéréotypes et préjugés associés aux malades atteints de cancer.…”
Section: Facteurs à L'origine Des Stéréotypes à L'égard Des Malades Aunclassified